2022
DOI: 10.3390/pharmaceutics14102070
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intranasal Administration in the Delivery of Antidepressant Active Ingredients

Abstract: As a mental disease in modern society, depression shows an increasing occurrence, with low cure rate and high recurrence rate. It has become the most disabling disease in the world. At present, the treatment of depression is mainly based on drug therapy combined with psychological therapy, physical therapy, and other adjuvant therapy methods. Antidepressants are primarily administered peripherally (oral and intravenous) and have a slow onset of action. Antidepressant active ingredients, such as neuropeptides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 194 publications
0
9
0
Order By: Relevance
“…As has been introduced, Oxt is produced both in the brain and the periphery. It is currently unknown whether plasma Oxt levels correlate with central Oxt release and whether peripheral administration can increase central Oxt levels because Oxt cannot readily cross the blood‐brain barrier (BBB) 66 . Recently, it was suggested that Oxt may reach the brain through transportation via the receptor for advanced glycation end products (RAGE) which is expressed in endothelial cells at the BBB 67,68 .…”
Section: Oxytocin and Oxytocin Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…As has been introduced, Oxt is produced both in the brain and the periphery. It is currently unknown whether plasma Oxt levels correlate with central Oxt release and whether peripheral administration can increase central Oxt levels because Oxt cannot readily cross the blood‐brain barrier (BBB) 66 . Recently, it was suggested that Oxt may reach the brain through transportation via the receptor for advanced glycation end products (RAGE) which is expressed in endothelial cells at the BBB 67,68 .…”
Section: Oxytocin and Oxytocin Receptormentioning
confidence: 99%
“…cross the blood-brain barrier (BBB). 66 Recently, it was suggested that Oxt may reach the brain through transportation via the receptor for advanced glycation end products (RAGE) which is expressed in endothelial cells at the BBB. 67,68 RAGE receptors have been shown to be crucial for the effect of exogenous Oxt on social behavior, such as bonding and parenting.…”
Section: Modulation Of Oxytocin By the Microbiomementioning
confidence: 99%
“…Traditional drug delivery methods, including intravenous and oral administration, have not yet achieved the goal of consistent brain delivery (Jin et al, 2022). However, intranasal delivery bypasses the BBB by delivering drugs directly from the nasal cavity to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, intranasal (IN) administration of nanosized drug delivery systems has been intensively investigated [ 23 , 24 ]. IN administration is a conventional noninvasive drug delivery approach for treating local nasal diseases such as infectious rhinitis, nasal polyposis, and sinusitis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%